ҚАЗАҚ ФОЛЬКЛОРЫНДАҒЫ ӘЙЙЕМГИ МОТИВЛЕР - Қобланов, Ж.Т.; Торткулбаева, Т.А. (FAN va JAMIYAT, 2025)
The article analyzes and examines the opinions expressed in the context of the cognitive nature of myths and their classification. It is clear that the culture and literature of antiquity occupy a special place in human society. The article provides a general overview of antiquity and explains its place in Kazakh literature. The fact that ancient motifs are found in abundance in the heritage of the Eastern peoples is presented and discussed from real works. Although there are general conclusions in the studies of ancient literature and literary monuments of the Kazakh people, it is known that the conclusion that its source is in the East, in the ancient literary traditions of the Kazakh people, has not been fully developed.